Diffusion of science and technology in the utilization of coffee husk waste at the Mu'min Mandiri Islamic Boarding School in Sidoarjo - Agus Prasetya; Beni Dwi Komara; Heri Cahyo Bagus Setiawan; Marti Winarni; Anggra Lita Sandra Dewi; Pismia Sylvi (Universitas Muhammadiyah Magelang, 2022)
The Mukmin Mandiri Islamic Boarding School Sidoarjo educates students to be involved in the coffee industry, with the target of instilling entrepreneurship and independence. Coffee waste and cow dung used as plant fertilizer, reducing the need for chemical fertilizers and lowering coffee production costs. The goals of this program are to 1) increase the knowledge of the students about cow dung and coffee husk waste management, and 2) increase their knowledge of cow dung and coffee husk as fertilizer. Lecture and discussion, technology transfer, and demonstrations are all method used. Students at the Mukmin Mandiri Islamic Boarding School can learn how to manage cow dung and coffee husk waste to increase coffee business income while also increasing independence and entrepreneurial spirit through the this program.